2020
DOI: 10.2147/ijn.s267007
|View full text |Cite
|
Sign up to set email alerts
|

<p>In vivo Bio-Distribution and Toxicity Evaluation of Polymeric and Lipid-Based Nanoparticles: A Potential Approach for Chronic Diseases Treatment</p>

Abstract: Introduction: Nanoparticles (NPs), as drug delivery systems, appear to be a promising tool for prolonged therapeutic strategies as they allow a controlled drug release over time. However, most of the studies found in the literature simply contemplate the use of a single or low number of dosages with low NPs concentrations. In the context of chronic diseases, like Alzheimer's disease, cancer or human immunodeficiency virus (HIV), where the therapeutic scheme is also chronic, studies with numerous repeated dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 64 publications
(69 reference statements)
1
20
0
1
Order By: Relevance
“…Increasing the sample size of each experimental group (table S2) will allow to assess further the reproducibility of our findings and better assess how tumor heterogeneity affects the proposed therapeutic strategy. Although past biodistribution and toxicity investigations of lipid nanoparticles with similar dosage to the one that we used in this study reported negligible toxicity (41)(42)(43), future studies in evaluating treatment outcomes (tumor growth and survival) in patient-derived tumors with and without known driver mutations, combined with extended toxicologic analysis under different LPH:siRNA doses, are warranted. Testing additional FUS exposures (e.g., lower harmonic emissions), ideally under closed-loop control (52)(53)(54)(55), combined with a more detailed assessment of the BBB phenotype (i.e., structure and function) and brain/tumor tissue (56,57) will allow to further define and refine the MB-FUS treatment window for safe and effective siRNA delivery in the brain TME.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Increasing the sample size of each experimental group (table S2) will allow to assess further the reproducibility of our findings and better assess how tumor heterogeneity affects the proposed therapeutic strategy. Although past biodistribution and toxicity investigations of lipid nanoparticles with similar dosage to the one that we used in this study reported negligible toxicity (41)(42)(43), future studies in evaluating treatment outcomes (tumor growth and survival) in patient-derived tumors with and without known driver mutations, combined with extended toxicologic analysis under different LPH:siRNA doses, are warranted. Testing additional FUS exposures (e.g., lower harmonic emissions), ideally under closed-loop control (52)(53)(54)(55), combined with a more detailed assessment of the BBB phenotype (i.e., structure and function) and brain/tumor tissue (56,57) will allow to further define and refine the MB-FUS treatment window for safe and effective siRNA delivery in the brain TME.…”
Section: Discussionmentioning
confidence: 89%
“…For these investigations, we used (i) a 0.5-MHz transducer with standard exposure settings (10-ms bursts, every 1 s for 1 min, at 475-kPa peak negative pressure in water), (ii) Optison (GE Healthcare) MBs with a dosage of 100 l/kg, and (iii) RhoB-LPH nanoparticles (5 mg/kg). The in vivo dosage of nanoparticle was decided on the basis of the dosages used in previous studies that showed that this nanoparticle dose led to minimal side effects (41)(42)(43). Fluorescence imaging of the excised brain 10 min after sonication indicated a 12fold increase in the extravasation of LPH in the FUS-treated region as compared to the non-FUS region (P < 0.0001) (Fig.…”
Section: Mb-fus Mediates Enhanced Penetration Of Lph:sirna Nanopartic...mentioning
confidence: 99%
“…injection, the following organs of the animals underwent histological examination: lymph node, spleen, liver, kidney, stomach, intestines, heart, lungs, brain, testis, and ovaries. These organs are usually analyzed in the in vivo studies of MNPs toxicity [ 29 , 30 ]. Similar results were obtained for mice and rats.…”
Section: Resultsmentioning
confidence: 99%
“…PLGA NPs are biocompatible, Food and Drug Administration (FDA) approved [ 54 ], and safe for repeat-dose exposure in vivo [ 55 ], being widely explored for incorporation in hydrogels for drug delivery. Wang et al (2021) developed a hydrogel composed of poly (ethylene glycol) diacrylate (PEGDA) and HA for the local delivery of paclitaxel for lung cancer therapy [ 26 ].…”
Section: Routes Of Drugs Administrationmentioning
confidence: 99%